PHYTOCHEMICALS OF ELAEOCARPUS WITH THEIRTHERAPEUTIC VALUE: A REVIEW - AMIT DADHICH; ANIRUDHA RISHI; GARGI SHARMA; SUBHASH CHANDRA (International Journal of Pharma and Bio Sciences, 2013)
Elaeocarpus is a genus of evergreen broad-leaved trees and shrubs widely distributed in warm regions belonging to family Elaeocarpaceae. This review consists of all publications relevant to pharmaceutical and pharmacological activity of Elaeocarpus genus that were identified by the authors. Various different methods used in this study prevent any kind of statistical pooling in results. tudies indicate that various Elaeocarpus species contain chemical constituents such as alkaloids, flavonoids, glycosides, tannins, triterpenes, fatty acids, ellagic acid derivatives and cytotoxic compounds. Studies also indicate different therapeutic activity of Elaeocarpus such as antiasthamatic, anxiolytic, antidepressant, antidiabetic and various other activities. All research work on Elaeocarpus reveals the immense medicinal value of this genus but still various Elaeocarpus species should be studied more extensively to confirm these results and reveal other potential medicinal values.